Blood zinc and copper concentrations in criminal and noncriminal schizophrenic men - Tokdemir, M; Polat, SA; Acik, Y; Gursu, F; Cikim, G; Deniz, O (Taylor & Francis Inc, 2003)
This study investigated the effects of zinc and copper on the behavior of schizophrenic patients by comparing blood zinc and copper levels in criminal and noncriminal schizophrenic patients. Of the total 88 subjects, 44 were patients with schizophrenia and no criminal record who were being treated at the Elazig Mental Hospital and 44 were schizophrenic patients who had committed a crime and were sent to the same hospital upon a court order for monitoring, detention, and treatment. Of the subjects with criminal records, 31 (70%) had committed a violent crime and 13 (30%) had committed a nonviolent crime. The mean plasma zinc value was 68+/-1.55 mug/dL in the criminal subjects and 81+/-2.73 mug/dL in the noncriminal subjects ( p =.001). The mean serum copper value was 104+/-1.80 mug/dL in criminal subjects and 93+/-2.92 mug/dL in noncriminal subjects ( p =.02). Mean plasma zinc values were significantly lower in criminal subjects when compared to noncriminal subjects, while mean serum copper values were significantly higher in criminal subjects than noncriminal subjects.
Keywords: copper; male offender; schizophrenia; zinc